2013
DOI: 10.1164/rccm.201307-1200oc
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nontuberculous Mycobacterial Infections and Associated Chronic Macrolide Use among Persons with Cystic Fibrosis

Abstract: Rationale: Persons with cystic fibrosis (CF) are at high risk of nontuberculous mycobacterial (NTM) infection, with treatment requiring prolonged multidrug regimens that include macrolides. Although macrolides, specifically azithromycin, are used in the management of patients with CF with chronic Pseudomonas, macrolide-resistant NTM infections are of growing concern. Objectives: To evaluate the relationship between chronic macrolide use and NTM infection among patients with CF included in the 2011 CF Patient R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 23 publications
8
95
0
1
Order By: Relevance
“…6,500 patients with CF and negative AFB cultures before entry, 191 patients had fi rst positive NTM cultures during the study for either MAC or M abscessus and were deemed incident cases. 59 These patients were signifi cantly less likely to have used azithromycin before their NTM diagnosis, and patients with the longest azithromycin use were least likely to have PNTM. For now, however, patients considered for long-term macrolide monotherapy (eg, those with CF) should be screened to exclude PNTM before starting therapy.…”
Section: Choice Of Macrolidementioning
confidence: 93%
“…6,500 patients with CF and negative AFB cultures before entry, 191 patients had fi rst positive NTM cultures during the study for either MAC or M abscessus and were deemed incident cases. 59 These patients were signifi cantly less likely to have used azithromycin before their NTM diagnosis, and patients with the longest azithromycin use were least likely to have PNTM. For now, however, patients considered for long-term macrolide monotherapy (eg, those with CF) should be screened to exclude PNTM before starting therapy.…”
Section: Choice Of Macrolidementioning
confidence: 93%
“…88,89 There are conflicting data regarding the potential for higher nontuberculous mycobacterial infection rates in individuals with CF on chronic azithromycin. 60, [90][91][92] There is insufficient evidence to recommend for or against the chronic use of azithromycin in preschoolers with CF. …”
Section: Azithromycinmentioning
confidence: 99%
“…Azithromycin use has recently been shown to block autophagy, suggesting that it has the potential to predispose patients with CF to mycobacterial infection (39), although this effect has not been seen in case-control studies (29,40). In addition, a recent nested case-control study by Binder and colleagues showed that patients with CF with incident NTM infections were less likely to have had chronic azithromycin treatment in the last year (41). Azithromycin was used in about one third of our subjects equally across the three outcome groups and was not associated with worse clinical outcomes.…”
Section: Original Researchmentioning
confidence: 99%